PENGARUH TERAPI NATURE SOUND TERHADAP TINGKAT STRES MAHASISWA PROFESI STIKES HAMZAR LOMBOK TIMUR - Jaya, Ilham; Rosidi, Ahyar (LPPM Universitas Sari Mulia, 2025)
Background: During this process, nursing students are faced with field practice and various reports required by every student in the nursing program. This can trigger various disorders, one of which is stress. Objective:. This study aims to determine the